Analisis Strategi Peningkatan Pendapatan Pelaku Usaha Mikro Kecil dan Menengah di Kabupaten Manokwari - Yopi Suabey; Halomoan Hutajulu (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2025)
This study aims to analyze the income level of noken (traditional Papuan woven bag) business actors in Manokwari Regency, identify the inhibiting and supporting factors in the empowerment process of cooperatives and noken business actors, and formulate appropriate strategies to increase the income of noken sellers in Manokwari Regency. The analytical methods used in this research consist of two stages: calculation of total production costs to measure the net income of craftsmen, and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify internal and external factors affecting the noken handicraft business. Data collection was carried out through observation, interviews, and documentation involving 27 noken craftsman respondents selected through purposive sampling with the criterion of having been in business for at least one year. Based on the results of the discussion, it can be concluded that the average income of noken craftsmen per production cycle is IDR 4,617,308 with a net income after deducting costs of IDR 4,070,769, where the revenue received is the product of the number of noken produced multiplied by the selling price at the time of production. The development strategy for the noken bag handicraft industry is based on two approaches: a strategy based on internal-external matrix analysis and a combination of SWOT matrix strategies, which shows that the priority strategy to be applied is the SO (Strengths-Opportunities) strategy, which utilizes strengths to take advantage of opportunities through three main indicators, namely capital, raw materials, and marketing. Noken sellers have several significant strengths such as easy access to raw materials, high skills, and low production costs, and can take advantage of existing opportunities including supportive government policies and increasing demand for noken bags. However, they also face weaknesses such as a lack of understanding of financial literacy and digital marketing, as well as threats from competition with modern bags and difficulties in obtaining natural raw materials, thus requiring a comprehensive strategy to overcome weaknesses and threats while maximizing existing strengths and opportunities. Keywords: Strategy, Income, MSMEs, Noken, SWOT Analysis